2020
DOI: 10.4149/bll_2020_068
|View full text |Cite
|
Sign up to set email alerts
|

Does the platelet‑to‑lymphocyte ratio have a prognostic effect in patients with myelodysplastic syndrome?

Abstract: INTRODUCTION: Myelodysplastic syndromes (MDS) include various hematologic abnormalities characterized by chronic cytopenia due to disruption in cellular differentiation. This study aims to evaluate the prognostic value of PLR in patients with MDS. MATERIAL AND METHODS: Clinical-laboratory fi ndings and the results of bone marrow biopsies of MDS patients before treatment were recorded. p value of < 0.05 was considered statistically signifi cant. SPSS version 20.0 was used for statistical analysis. RESULTS: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…18 A higher PLR (≥22.4) was suggested as an inferior predictor for OS in a study by Shi et al 19 that included 213 patients with MDS. Yikilmaz et al 20 reported that a decreased PLR (≤46) was associated with MDS subtypes featuring multilineage dysplasia in univariate analyses but was not associated with OS in a cohort of 62 MDS patients. In our study, we concluded that a higher PLR ≥ 213.2 was an independent risk factor for OS in MDS.…”
Section: Discussionmentioning
confidence: 99%
“…18 A higher PLR (≥22.4) was suggested as an inferior predictor for OS in a study by Shi et al 19 that included 213 patients with MDS. Yikilmaz et al 20 reported that a decreased PLR (≤46) was associated with MDS subtypes featuring multilineage dysplasia in univariate analyses but was not associated with OS in a cohort of 62 MDS patients. In our study, we concluded that a higher PLR ≥ 213.2 was an independent risk factor for OS in MDS.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, high levels of ACL were associated with a specific subgroup of MDS patients with ring sideroblasts, known to have a good prognosis [ 69 ]. MDS of multilineage dysplasia, on the other hand, was associated with a lower level of PLR [ 70 ]. However, lymphocyte counts were low in therapy-related MDS.…”
Section: Myeloid Malignanciesmentioning
confidence: 99%